2019
DOI: 10.1245/s10434-019-07299-7
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of Neoadjuvant Chemotherapy with S-1 Plus Docetaxel for Locally Advanced Gastric Cancer: A Propensity Score-Matched Analysis

Abstract: Background Postoperative docetaxel plus S-1 (DS) chemotherapy is expected to be the standard therapeutic strategy for pStage III gastric cancer based on the results of the JACCRO GC-07 study. Neoadjuvant chemotherapy (NAC) is thought to have several advantages over adjuvant settings. Objective This study aimed to compare the efficacies of NAC DS and the surgery-first strategy for advanced gastric cancer patients with D2 gastrectomy. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…Excellent outcomes could be expected from surgery alone when gastric cancer is diagnosed at early stage. However, in locally advanced GC patients, operation could not always lead to a satisfactory consequence, even with postoperative therapy [2]. Neoadjuvant chemotherapy (NCT) improves R0 resection rate and prognosis when compared with surgery alone or surgery with postoperative therapy [3], but the outcomes are sometimes unpredictable due to the differences in many factors such as tumor differentiation and Lauren classification.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent outcomes could be expected from surgery alone when gastric cancer is diagnosed at early stage. However, in locally advanced GC patients, operation could not always lead to a satisfactory consequence, even with postoperative therapy [2]. Neoadjuvant chemotherapy (NCT) improves R0 resection rate and prognosis when compared with surgery alone or surgery with postoperative therapy [3], but the outcomes are sometimes unpredictable due to the differences in many factors such as tumor differentiation and Lauren classification.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been revealed that the distribution of programmed cell death ligands (PD‐L) differs depending on the type of head and neck squamous cell carcinoma (HNSCC) . In HNSCC patients, PD‐L2 expression has been reported to be greater than that of PD‐L1 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have demonstrated the prognostic signi cance of conversion surgery after chemotherapy in patients with stage IV gastric cancer [9][10][11][12]. Conversely, neoadjuvant chemotherapy (NAC) has been found as a promising therapeutic strategy in patients with locally advanced gastric cancer, such as those with macroscopic type 4 tumor, large type 3 tumor, bulky lymph node metastasis, and clinically stage III [13][14][15][16][17]. However, the indication and prognostic signi cance of conversion surgery or NAC remain uncertain in patients with type 4 gastric cancer.…”
Section: Introductionmentioning
confidence: 99%